Development of a C Language Education Instructor Training Course Using Animated Characters - Lim, Dongkyun; Eun Lee, Ji; Um, Gijun; Moon, Dosik (International Journal of Engineering and Technology, 2018)
The purpose of this study is to develop online lecture contents that can effectively teach C language to 5th, 6th grade or middle school students. Unlike existing cyber lectures, the proposed contents were created by using animated characters to help beginner level students learn C language through interesting storytelling, role playing games, and card games. This C language education contents were devel-oped for teachers to effectively educate elementary and middle school students who are presumed to have no prior knowledge of C lan-guage. The proposed contents motivate young learners to learn the introductory concepts of C language through the animated characters based on storytelling, more than using mere focus on rote memorization.Â